2015
DOI: 10.1016/j.rbmo.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, fatness, educational level and snuff consumption as determinants of semen quality: findings of the ActiART study

Abstract: In this study, the association between physical activity and other potential determinants, objectively measured by accelerometry, was examined. Sixty-two men attending an infertility clinic participated in the study. Obese men (body mass index ≥ 30) and those with a waist circumference 102 cm or more had lower semen volume than the other men (P < 0.05). Higher values in sperm parameters were observed in participants who completed university studies and those who did not consume snuff, compared with the other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
2
29
0
3
Order By: Relevance
“…Nevertheless, the promotion of moderate-to-vigorous PA may improve semen parameters, sperm DNA integrity, impaired seminal markers of inflammation, and oxidative stress [45,46]. Interestingly, the impact of different intensities showed an inverted U-shape association between PA and semen quality [47,48]. Also, other studies supported this finding, suggesting poorer semen quality in sedentary [7,16,49] or highly active men [42] compared with recreationally or moderate physically active men.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, the promotion of moderate-to-vigorous PA may improve semen parameters, sperm DNA integrity, impaired seminal markers of inflammation, and oxidative stress [45,46]. Interestingly, the impact of different intensities showed an inverted U-shape association between PA and semen quality [47,48]. Also, other studies supported this finding, suggesting poorer semen quality in sedentary [7,16,49] or highly active men [42] compared with recreationally or moderate physically active men.…”
Section: Discussionmentioning
confidence: 91%
“…One small study of Swedish men seeking infertility treatment found reduced semen quality in snuff users, 15 though another study of Swedish military conscripts did not show an association between snuff use and semen parameters. 16 We did not observe an effect of male smokeless tobacco use on TTP compared with never users of tobacco; however, we did observe male smokeless tobacco users had a shorter TTP compared with cigarette users.…”
Section: Discussionmentioning
confidence: 95%
“…45,46 In light of the call for smokeless tobacco use as a harm reduction tool for smokers, increasing smokeless tobacco use among young adults in the United States, and the relatively greater use of smokeless tobacco in other countries, further investigations into the potential reproductive toxicity of smokeless tobacco are warranted. Scandinavian populations may be well suited for future work on this topic as smokeless tobacco use is common, 15 even among females, 47 and surveillance systems for reproduction (eg, semen analysis among military conscripts and national birth and health registers) are already in place. Additionally, elucidating the biological mechanisms by which tobacco products may interfere with couples' biological capacity to conceive will provide more information of the potential harms of tobacco use, both combustible and noncombustible, in couples trying to conceive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether there is a relationship between snuff consumption and impaired male reproduction is still unclear, although there is evidence pointing in that direction (35). It is, however, known that smoking has negative effects on semen quality (36), and Swedish studies indicate that maternal snuff use in early pregnancy is associated with an increased risk of oral clefts in the child (37) and stillbirth (38).…”
Section: Discussionmentioning
confidence: 99%